Last Century Warming Over the Canadian Atlantic Shelves Linked to Weak Atlantic Meridional Overturning Circulation. Issue 22 (20th November 2018) - Thibodeau, Benoit; Not, Christelle; Hu, Jiang; Schmittner, Andreas; Noone, David; Tabor, Clay; Zhang, Jiaxu; Liu, Zhengyu
Abstract: The Atlantic meridional overturning circulation (AMOC) is a key component of the global climate system. Recent studies suggested a twentieth‐century weakening of the AMOC of unprecedented amplitude ( 15%) over the last millennium. Here we present a record of δ 18 O in benthic foraminifera from sediment cores retrieved from the Laurentian Channel and demonstrate that the δ 18 O trend is linked to the strength of the AMOC. In this 100‐year record, the AMOC signal decreased steadily to reach its minimum value in the late 1970s, where the weakest AMOC signal then remains constant until 2000. We also present a longer δ 18 O record of 1, 500 years and highlight the uniqueness of the last century δ 18 O trend. Moreover, the Little Ice Age period is characterized by statistically heavier δ 18 O, suggesting a relatively weak AMOC. Implications for understanding the mechanisms driving the intensity of AMOC under global warming and high‐latitude freshwater input are discussed. Plain Language Summary: Oceanic circulation in the North Atlantic transports huge amounts of water, heat, salt, carbon, and nutrients around the globe. As such, changes in the strength of oceanic currents can yield profound changes in both North American and European climate, in addition to affecting the African and Indian summer monsoon rainfall. In this study, we used geochemical evidence to highlight a slowdown in the North Atlantic Ocean circulation over the last century. This change appears to be unique over the last 1, 500 years and could be related to global warming and freshwater input from ice sheet melt. Based on our data, we also suggest that the period often called "The Little Ice Age" was characterized by a slowdown, of less amplitude than the modern weakening, in the North Atlantic Ocean circulation. Thus, our results contribute to ongoing investigations of the state of the circulation in the North Atlantic by providing a robust reconstruction of its variability over the last 1, 500 years. Key Points: The oxygen isotope in the Laurentian Channel can trace variations in the subsurface western North Atlantic circulation The twentieth century is characterized by the weakest Atlantic meridional overturning circulation of the last 1, 500 years The Little Ice Age is also characterized by relatively higher oxygen isotope, which can be linked to a weaker AMOC